Analysis of Factors Affecting Consumer Purchase Behavior: Study in Muslim communities who shop online through the Shopee Application - suherman, usep deden (Li Falah: Journal of Islamic Economics and Business, 2021)
This study aims to determine and analyze what factors influence consumer buying behavior in the era of citizen 4.0 and the most dominant influences on consumer buying behavior in citizen 4.0. This research uses descriptive and explanatory survey methods. Sampling was carried out using the Accidental Sampling sample technique. The data analysis technique used is factor analysis. The findings of this study are factors such as availability and price factors, promotion factors, comfort factors, varieties and comparison factors, after-sales service factors, and connectivity factors that influence consumer purchasing behavior in the era of citizen 4.0. Besides that, variety and comparison factors are the most dominant factors affecting consumer buying behavior in the age of citizen 4.0, followed by availability and price factors, comfort factors, promotion factors, after-sales service factors, and connectivity factors.